Development of Edpuzzel as an Interactive Media in Muraja'ah Program for Junior High School Students - Sari, Lisa Candra; Kustati, Martin; Sepriyanti, Nana; Novrianti, Novrianti (International Journal of Educational Narratives, 2024)
Background. One of the factors that influence the success of the implementation of learning programs is the teacher, the teacher is believed to be one of the dominant factors that determine the level of student success in achieving results in the learning process Purpose. This study aims to develop Edpuzzle as an interactive media that matches the eligibility criteria of media and materials to improve students' muraja'ah abilities. Method. This type of research is R&D with a 4D development model whose stages are. Define, Design, Development and Disseminate. Results. Overall, the interactive learning video media product tawaasilul aayat method in middle class tahfizh subjects at SMPs IT Tahfizh Adzikra Padang is "Very Valid" so it deserves to be tested in tahfizh learning, especially in the field of muraja'ah. Conclusion. Based on the data processing process carried out, this study showed the results obtained by 3.62 or 72.3% of the first stage of media experts with the category "Valid", 4.15 or 83% of the second media experts of the first stage with the category "Very Valid".